Transferrin Receptor Functionally Marks Thermogenic Adipocytes - Qiu, Jin; Zhang, Zhiyin; Wang, Sainan; Chen, Yanru; Liu, Caizhi; Xu, Sainan; Wang, Dongmei; Su, Junlei; Ni, Mengshan; Yu, Jian; Cui, Xiangdi; Ma, Lu; et al. (Frontiers in Cell and Developmental Biology, 2020)
Background: Thermogenic adipocytes, including beige and brown adipocytes, are critical for thermogenesis and energy homeostasis. Identification of functional cell surface marker of thermogenic adipocytes is of significance for potential application in biological and clinical practices. Methods: With a combination of RNA-sequencing of in vivo and in vitro models, we identified Transferrin Receptor (Tfr1), a receptor specialized for cellular iron uptake, as a previously unappreciated cell surface molecule for thermogenic adipocytes compared to white adipocytes. The alternation of Tfr1 levels under physiological and pathological stimuli were assessed and the mitochondria functionality, browning capacity and iron metabolism of mature adipocytes was examined with Tfr1 knockdown. Results: Tfr1 was expressed predominantly in thermogenic adipocytes versus white adipocyte and its expression levels were tightly correlated with the activation or inhibition status of thermogenic adipocytes under external stimuli. Besides, Tfr1 gene deficiency in thermogenic adipocytes led to reduced thermogenic gene programs and mitochondrial integrity. Conclusion: Tfr1 functionally marks thermogenic adipocytes and could serve as a potential thermogenic adipocytes surface marker.